2010
DOI: 10.1073/pnas.1003345107
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating NY-ESO-1–specific CD8 + T cells are negatively regulated by LAG-3 and PD-1 in human ovarian cancer

Abstract: NY-ESO-1 is a "cancer-testis" antigen frequently expressed in epithelial ovarian cancer (EOC) and is among the most immunogenic tumor antigens defined to date. In an effort to understand in vivo tolerance mechanisms, we assessed the phenotype and function of NY-ESO-1-specific CD8 + T cells derived from peripheral blood lymphocytes (PBLs), tumor-infiltrating lymphocytes (TILs), and tumorassociated lymphocytes (TALs) of EOC patients with NY-ESO-1-expressing tumors, with or without humoral immunity to NY-ESO-1. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
623
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 768 publications
(655 citation statements)
references
References 23 publications
13
623
0
3
Order By: Relevance
“…Together, these features suggest that TIL in ovarian cancer may have experienced prolonged exposure to their cognate antigen and, as a consequence, may be functionally exhausted. In support of this notion, prior studies have shown that NY-ESO-1-specific CD8 þ TIL from ovarian cancer patients frequently express PD-1 and are functionally impaired compared with their counterparts in peripheral blood (20). Moreover, ovarian tumor cells have been reported to express high levels of PD-L1 (21,22).…”
Section: Introductionsupporting
confidence: 49%
“…Together, these features suggest that TIL in ovarian cancer may have experienced prolonged exposure to their cognate antigen and, as a consequence, may be functionally exhausted. In support of this notion, prior studies have shown that NY-ESO-1-specific CD8 þ TIL from ovarian cancer patients frequently express PD-1 and are functionally impaired compared with their counterparts in peripheral blood (20). Moreover, ovarian tumor cells have been reported to express high levels of PD-L1 (21,22).…”
Section: Introductionsupporting
confidence: 49%
“…TIL and PBMC from LM-CRC were labeled with 0.1 µM carboxyfluorescein diacetate succinimidyl ester (CFSE, Invitrogen); afterwards 10 5 TIL or PBMC were cultured in 200 µl complete medium in each well of a 96-well round-bottom culture plate and stimulated with anti-human CD3/CD28 dynabeads (Gibco-Life Technologies AS, Norway) at a cell: bead ratio of 10:1, in the presence or absence of 10 μg/ml antagonistic monoclonal antibodies against human PD-L1 (clone 5H1, kindly provided by Dr. Haidong Dong, Mayo Clinic College of Medicine, 59 ) TIM3 (clone F38-2E2, Biolegend, San Diego, USA, 60 , 61 ) LAG3 (clone 17B4, AdipoGen, Liestal, Switzerland 62 ) or CTLA4 (clone BNI3, Beckman Coulter, Marseille, France, 63 ) or isotype-matched control antibodies (mIgG1 and mIgG2 a, Biolegend, London, UK). In preliminary experiments a cell: bead ratio of 10:1 was established to provide sub-optimal stimulation of T cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the function of tumor antigen-specific CD8 þ T cells was significantly augmented by dual blockade of LAG3 and PD-1, thus, possibly represented a highly promising immune-based strategy in cancer treatment. 38,39 There are multiple clinical trials trying to translate combination modality into clinical practice (Table 1).…”
Section: Combination Strategiesmentioning
confidence: 99%